2012
DOI: 10.1016/j.jvs.2011.11.134
|View full text |Cite
|
Sign up to set email alerts
|

Changes in baroreceptor sensitivity after eversion carotid endarterectomy

Abstract: E-CEA might have a decreasing influence on BRS, leading to increased sympathetic activity. Investigations of the longer-term effects of impaired BRS are warranted. These findings should be interpreted with caution, noting the limitation of an absent control group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
38
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 33 publications
0
38
0
3
Order By: Relevance
“…[6,11,12] Several studies have demonstrated that hypertension caused by baroreflex dysfunction is associated with higher levels of cardiovascular and neurological mortality and morbidity. [1][2][3]13] Untreated hypertension is often considered to be one of the independent risk factors for poor outcome following CEA. While certain studies describe a positive relation between perioperative hypertension and the risk of poor neurological outcome or death after CEA, other studies have not found such a relationship.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…[6,11,12] Several studies have demonstrated that hypertension caused by baroreflex dysfunction is associated with higher levels of cardiovascular and neurological mortality and morbidity. [1][2][3]13] Untreated hypertension is often considered to be one of the independent risk factors for poor outcome following CEA. While certain studies describe a positive relation between perioperative hypertension and the risk of poor neurological outcome or death after CEA, other studies have not found such a relationship.…”
Section: Discussionmentioning
confidence: 99%
“…[1,3,16,17] A several variety of causes described in numerous studies as factors which significantly contribute to the development of hypertension include the severity and side of carotid stenosis; prior ipsilateral hemispheric neurological symptoms (stroke or TIA); the presence of contralateral disease; history of previous ipsilateral or contralateral carotid surgery; and the surgical techniques being used. [6,16,[18][19][20][21] Furthermore, several studies have defined preoperative neurological deficits as independent predictors of hypertension following CEA.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations